Anti-SARS-CoV-2 antibodies following vaccination are associated with lymphocyte count and serum immunoglobulins in SLE. (March 2023) - Reynolds, John A; Faustini, Sian E; Tosounidou, Sofia; Plant, Tim; Ubhi, Mandeep; Gilman, Rebecca; Richter, Alex G; Gordon, Caroline
Objectives: Patients with Systemic Lupus Erythematosus are known to have dysregulated immune responses and may have reduced response to vaccination against COVID-19 while being at risk of severe COVID-19 disease. The aim of this study was to identify whether vaccine responses were attenuated in SLE and to assess disease- and treatment-specific associations. Methods: Patients with SLE were matched by age, sex and ethnic background to healthcare worker healthy controls (HC). Anti-SARS-CoV-2 spike glycoprotein antibodies were measured at 4–8 weeks following the second COVID-19 vaccine dose (either BNT162b2 or ChAdOx1 nCoV-19) using a CE-marked combined ELISA detecting IgG, IgA and IgM (IgGAM). Antibody levels were considered as a continuous variable and in tertiles and compared between SLE patients and HC and associations with medication, disease activity and serological parameters were determined. Results: Antibody levels were lower in 43 SLE patients compared to 40 HC ( p < 0.001). There was no association between antibody levels and medication, lupus disease activity, vaccine type or prior COVID infection. Higher serum IgA, but not IgG or IgM, was associated with being in a higher anti-SARS-CoV-2 antibody level tertile (OR [95% CI] 1.820 [1.050, 3.156] p = 0.033). Similarly, higher lymphocyte count was also associated with being in a higher tertile of anti-SARS-CoV-2 (OR 3.330 [1.505, 7.366] p = 0.003) Conclusion: Patients with SLE have lower antibody levels following 2 doses of COVID-19 vaccines compared to HC. In SLE lower lymphocyte counts and serum IgA levels are associated with lower antibody levels post vaccination, potentially identifying a subgroup of patients who may therefore be at increased risk of infection.